Reliance Hazira - Reliance Industries Limited (2022)
From his days in Aden, Shri Dhirubhai Ambani nurtured a dream to establish a refinery. In 1988, Shri Dhirubhai Ambani initiated efforts to establish a petrochemical complex at Hazira, near Surat. In 1991, the first phase of the Reliance Hazira project was commissioned to manufacture a wide range of polymers, polyesters, and petrochemicals.